Enhancing Transparency and Accountability in Public Services Through Information Technology: A Case Study of Timor-Leste’s Ministry of Justice - Petu, Vitalis; Amaral, Adolmando Soares; Nahak, Martinus; Gusmão, Fernando Dias; M. Martins5, Leonito (International Journal of Social Service and Research, 2025)
This study explores the novel application of the Ajendamento online scheduling system in Timor-Leste’s passport services, addressing gaps in prior research by focusing on its dual role in enhancing transparency and accountability while confronting unique local challenges. Unlike broader e-government studies, this research provides empirical evidence from a least-developed country (LDC) context, where infrastructural and literacy barriers significantly impact digital adoption—a dimension underexplored in existing literature. Using a qualitative case study design, the study analyzes interviews with 12 stakeholders, document reviews, and observational data from Timor-Leste’s Ministry of Justice. Findings reveal that the Ajendamento system reduces broker interference, improves service efficiency, and fosters procedural transparency. However, persistent issues such as uneven internet access (54.2% penetration), low digital literacy (especially among rural and elderly populations), and institutional capacity gaps (e.g., 26% contracted staff, limited training) hinder equitable implementation. These challenges contrast with studies in more advanced digital economies, highlighting the critical need for context-specific solutions. The study contributes to e-government theory by emphasizing the interplay between technological systems and socio-institutional readiness in LDCs, a nuance absent in Heeks’ (2002) generalized frameworks. Practical implications include targeted investments in infrastructure, literacy campaigns, and inter-agency collaboration to ensure inclusive digital transformation. By bridging the gap between policy aspirations and grassroots realities, this research offers a model for similar settings globally.